2018
DOI: 10.1063/1.5031799
|View full text |Cite
|
Sign up to set email alerts
|

Very small tail state formation in Cu2ZnGeSe4

Abstract: We find that coevaporated Cu2ZnGeSe4 has an ideal bandgap for solar cells (1.39 ± 0.01 eV) and shows quite reduced tail state absorption with a very low Urbach energy of 28 meV, which is far smaller than those of more studied Cu2ZnSnSe4 and Cu2ZnSnS4. The small tail states in Cu2ZnGeSe4 are found to originate from almost perfect cation ordering, while unusual tail state generation occurs in the Sn-based quaternary compounds by extensive cation substitution. Quite remarkably, the crystal total energy derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 33 publications
5
31
0
Order By: Relevance
“…Among the most relevant pure Ge kesterite results, Schnabel et al reported efficiencies exceeding 5% for a sulfo-selenide CZGSSe (E g ∼1.5 eV) solar cell [124], while for the selenide CZGSe (Eg∼1.4 eV) compound, Sahayaraj et al published a 5.5% efficiency device with a remarkable V OC of 744 mV [125]. Intriguingly, the Ge based kesterite showed less electrical losses from band tailing/electrostatic potential fluctuations compared to Ge free devices [125,126]. However, the main limiting factors were linked to a high series resistance, leading to imperfect current collection and a high interface recombination [127].…”
Section: Germanium (Ge)mentioning
confidence: 99%
“…Among the most relevant pure Ge kesterite results, Schnabel et al reported efficiencies exceeding 5% for a sulfo-selenide CZGSSe (E g ∼1.5 eV) solar cell [124], while for the selenide CZGSe (Eg∼1.4 eV) compound, Sahayaraj et al published a 5.5% efficiency device with a remarkable V OC of 744 mV [125]. Intriguingly, the Ge based kesterite showed less electrical losses from band tailing/electrostatic potential fluctuations compared to Ge free devices [125,126]. However, the main limiting factors were linked to a high series resistance, leading to imperfect current collection and a high interface recombination [127].…”
Section: Germanium (Ge)mentioning
confidence: 99%
“…The tail state formation in a-Si:H is caused by the random nature of the amorphous network [34]. Quite large tail absorption in CZTSe and CZTS has been attributed to cation disorder (i.e., Cu/Zn/Sn mixing) [35,36], while the tail state generation is negligible in Cu 2 ZnGeSe 4 (CZGSe) due to the suppression of the cation mixing [36]. been incorporated into the calculation by adopting experimental data, while an unrealistic step function with E U = 0 eV is assumed for the light absorption in the SQ model.…”
Section: Shadow Loss 5% Neglectedmentioning
confidence: 99%
“…14 Recently, Dhawale et al reported an improvement in the V oc -deficit mainly due to the reduced band tailing obtained by controlling the Ge/(Sn + Se) ratio. 18 Nagaya et al reported the advantages of Ge in CZTS, 19 with a very small tail state formed in CZGSe compared to the large band tailing observed in CZTS and CZTSe. In a previous study, our low-temperature Time-Resolved Photoluminescence (TRPL) Cu 2 ZnGeSe 4 data suggest that a dominant contribution to the observed band tailing in CZT(S,Se) samples comes from the electrostatic potential fluctuations which is totally absent in the Cu 2 ZnGeSe 4 absorber.…”
Section: Introductionmentioning
confidence: 99%